PENGGUNAAN MEDIA ILUSTRASI POP-UP SEJARAH DALAM PEMBELAJARAN IPS DI SD NEGERI BATURSARI - Yulita Dewi Purmintasari; Eka Jaya PU (Khazanah Pendidikan, 2017)
This study aims: (1to know the process of learning social science in SD Negeri Batursari, (2) to know the use of illustration pop-up media in relieve the teacher to foster student‟s understanding toward the social science subject. This study was conducted in SD Negeri Batursari by using qualitative research strategies. The technique in collecting data were interview, direct observation, questionnaires and research document. The data validated by using triangulation researcher, theoretical and methodological. The technique using data collection, data reduction, and data presentation and conclusion/ verification. The result showed that fourth and rade students SD Negeri Batursari very anthusiastic in participating learning social science, students were formed into small groups and students talk to each other discussing visula messages in pop-up media. Illustration pop-up media is very helpful the teacher inleraning social science, it can be seen when students most easily to understand the material by looking at the illustration in the material. The syudents helped with the media as if the were in the illustration. Keywords: Pop-Up Media, Social Science Learning